THE ROLE OF BRAND IMAGE IN SKINCARE CONSUMPTION DECISIONS: EVIDENCE FROM SANTRI OF MAMBAUL ULUM BATA-BATA ISLAMIC BOARDING SCHOOL - Qaiyim Asy’ari; Abdul Bari; Nurul Tayyibah; Ach Mahfud Abd Qadir (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to analyze the influence of brand image on skincare consumption decisions among students at Mambaul Ulum Bata-Bata Islamic Boarding School. This research uses a quantitative approach with a survey method by distributing questionnaires to respondents. The number of respondents in this study was 100 students who use or are familiar with skincare products. The data analysis techniques used include validity tests, reliability tests, simple linear regression analysis, correlation analysis, and hypothesis testing using the t-test. The results show that brand image has a positive and significant influence on skincare consumption decisions. This is indicated by the t-count value which is higher than the t-table value at a significance level of 0.05, so the research hypothesis is accepted. Therefore, it can be concluded that brand image is one of the important factors influencing students' decisions in choosing and using skincare products.